American trypanosomiasis and associated risk factors in owned dogs from the major city of Yucatan, Mexico. Issue 1 (December 2015) - Jiménez-Coello, Matilde; Acosta-Viana, Karla; Guzmán-Marín, Eugenia; Bárcenas-Irabién, Alejandra; Ortega-Pacheco, Antonio
Abstract Background The American trypanosomiasis is a zoonosis caused by the protozoaTrypanosoma cruzi (T. cruzi ). The disease is widely distributed throughout the American continent, affecting a wide range of hosts, including dogs. It is present in the canine population in the State of Yucatan, Mexico. However, no significant studies in owned dogs have been performed in the metropolitan area of Merida. A transversal study was conducted in 370 owned dogs from Merida, Yucatan, Mexico. Methods A cross-sectional study including 370 dogs was performed in a major city of Yucatan, Mexico, to detect IgG antibodies againstT. cruzi . A commercial ELISA test kit was used and a chi-square test used to evaluate associated risk factors; odds ratio (OR) and 95 % confidence interval (CI) were also estimated. Results The indirect ELISA and western blot (WB) tests were used to detect specific immunoglobulin G antibodies againstT. cruzi in serum samples. A prevalence of 12.2 % was found; age and area of residence were statistically associated with seropositivity in dogs (p <0.05). Conclusions Results from the present study suggests the presence and abundance of the vector in urban conditions where a high number of seropositive cases ofT. cruzi cases were found.